Brüchige Demarkationsformeln: über "methodischen Naturalismus", "NOMA" und "POMA" als Deutungen des Verhältnisses von Religion und Wissenschaft - Löffler, Winfried (Zeitschrift für katholische Theologie, 2011)
The slogans of »methodological naturalism« (MN) and of the nonoverlapping magisteria (NOMA) of religion and science were created to find a peaceful démarcation in the ongoing debates about the relation of faith and science. I will trace the historical backgrounds of these slogans and explain why they came under attack – interestingly from the very antagonist camps of creationism and Dawkinsstyle naturalism. In a nutshell, MN invites to very different interpretations, depending on different background assumptions and interests, and NOMA tends to misconceive the essence of religion. McGrath's proposai of partially overlapping magisteria (POMA) seems to be prima facie attractive, at least for a religious point of view, but at closer scrutiny lacks clarity. In sum, those slogans do not fulfill their supposed demarcation function. The concluding chapter sketches an account of a concordant relation between faith and science, drawing from some of McGrath's remarks and bringing the hidden common assumptions of faith and science into clearer focus.